Pengaruh Minat Baca Sejarah Terhadap Kegiatan Pembelajaran Peserta Didik dalam Aliran Filsafat Pendidikan Konstruktivisme - Nurul Febrian, Anisa; Safitri, Sani (Yayasan Sukma Bangsa, 2024)
The goal to be achieved in this article is to find out how reading interest in History are related to the learning activities of students at SMA Negeri 2 Unggul Sekayu. As we know History in the school curriculum is often underestimated and even ignored because it is considered not too important, unlike Biology, Chemistry, Mathematics, Economics, which are exact sciences whose usefulness is clearly visible in daily activities. In the learning process, the application of philosophy is very important, one of which is the philosophy of constructivism education where this flow applies active and student-based learning, students seek and interpret their own new knowledge or material. In fulfilling the data of this article, it was done by observing interviews with teachers and students at the school, and adding references from both journals and books.